Partnership Literacies: Who's Got the Camera?. Issue 2 (September 2017) - Boggs, George L.; Fendler, Rachel; Shields, Sara Scott; Tripp, Lisa M.; Pengelley, Ivanna Rebecca
Abstract: Often coauthored by university‐ and school‐based educators, preservice teachers, and youths, this department column considers how literacies are best developed through context‐crossing partnerships among university, school, and community constituents.